The Predictive value of serum glutathione S-transferase (GST-π), P-glycoprotein (PGP), P53, Ki-67 and breast cancer :Systematic review and meta-analysis: serum markers and breast cancer - zhang, nuan (Journal of Medical Biochemistry, 2025)
Objective: To evaluate the correlation between triple-negative breast cancer (TNBC) and drug-resistant protein expression, and to provide reference for improving the treatment of TNBC. Methods: The relevant literature was searched through PubMed, Web of Science, CNKI, WanFang data, along with VIP databases from 2010 to 2024. Literature screening together with data extraction were implemented by two researchers, and literature quality was evaluated. Meta-analysis was implemented on the extracted data by means of RevMan 5.3 software. Results: There were 7 literatures included, all of which were in English. Meta-analysis results revealed that, compared to non-TNBC, the expression rate of GST-π protein in TNBC was elevated [OR=3.41, 95% CI (2.21, 5.25), P<0.00001], the expression rate of Pgp protein in TNBC was elevated [OR=1.87, 95% CI (1.17, 2.98), P=0.008], the expression rate of P53 protein in TNBC was elevated [OR=3.65, 95% CI (2.25, 5.91), P<0.00001], the expression rate of Ki-67 in TNBC was elevated [OR=1.19, 95% CI (0.54, 1.84), P=0.0004], the expression rate of Topo grade Ⅰ in TNBC was no significance [OR=0.71, 95% CI (0.14, 3.51), P=0.67], the expression rate of Topo grade Ⅱ in TNBC was was no significance [OR=0.56, 95% CI (0.26, 1.21), P=0.14], the expression rate of Topo grade Ⅲ in TNBC was no significance [OR=1.13, 95% CI (0.15, 8.64), P=0.91], the DFS level in TNBC was elevated [OR=0.30, 95% CI (0.15, 0.59), P=0.0005], and the level of OS in TNBC was elevated [OR=0.17, 95% CI (0.11, 0.28), P<0.00001]. Conclusion: There are many drug-resistant proteins in triple-negative breast cancer, which can be more resistant to chemotherapy drugs, so it is necessary to detect drug-resistant proteins during chemotherapy treatment to obtain better clinical treatment effect.